Efektivitas Model Pembelajaran Hybrid Learning pada Teks Eksposisi Siswa Kelas X Madrasah Aliyah Ainul Hasan - Ahmad Zainullah; Endah Tri Wisudaningsih; Fatih Holis Ahnaf (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
Being a teacher is not an easy thing to apply knowledge to, but being a professional teacher is mandatory in order to produce educated successors to the nation. As a professional teacher, he will choose the right learning model for his students, the goal is to improve student learning outcomes and students quickly understand what the teacher has explained. This study aims to boost how effective the Hybrid Learning learning model is in exposition text in improving student learning outcomes of class X Madrasah Aliyah Ainul Hasan. The hybrid learning learning model is an option for implementing learning in this digital era from. The problems in this study, namely (1). What are the student learning outcomes before, after the implementation of the Hybrid Learning learning model, and (2). How is the effectiveness of the Hybrid Learning learning model? This research method is quantitative, using an experimental design on the exposition text of class X students in the pretest-posttest group. The population and sample used were all 31 students of class X Madrasah Aliyah Ainul Hasan. The results in this study were seen from the average results obtained before the implementation of Hybrid Learning 73.85, and after 86.91. The comparison of the results above shows that Hybrid Learning learning in exposition text is effective for improving student learning outcomes in class X Madrasah Aliyah Ainul Hasan.Keywords: Learning Model Effectiveness, Hybrid Learning, Exposition Text